Application of Color Doppler ultrasound in monitoring the effect of reducing the transjugular portosystem shunt due to hepatic encephalopathy: Case report - Dulovic, Dragan V. (Medicinski časopis, 2018)
Transjugular portosystemic shunt (TIPS) is interventional vascular radiology procedure, which represents a method of choice for reducing problems of patients with portent hypertension. However, in a number of patients as a late complication hepatic encephalopathy (HE) may occur, thus in that situation the reduction of lumen trough shunt’s flow is needed. In such patient cases, with Color Doppler ultrasound (CDU), we can determine the flow through shunt, before and after reduction of lumen. In this article is presented the case of patient, where after of using of TIPS, the hepatic encephalopathy occurred and after the reduction of lumen has been conducted. The effects of procedure are followed by Color Doppler ultrasound. Conclusion: CDU as simple and non-invasive, with high rate of specifics and sensitivity, represent adequate radiology method, which can be used for monitoring conditions of patient with TIPS, more precise for monitoring the effects of reduction of shunt’s lumen.